PERAN IRAN HUMAN RIGHTS (IHR) DALAM MENGGALANG DUKUNGAN UNTUK KASUS MAHSA AMINI - Bunga Annisa Siregar; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The death of an Iranian female activist, Mahsa Amini, after being arrested by Iran's moral police for not wearing the headscarf prompted demonstrations by the Iranian people in September in 2022. One of the non-governmental organizations that participated in raising aid for the death of Mahsa Amini is Iran Human Rights (IHR). IHR is a non-governmental organization based in Oslo, Norway that focuses on human rights in Iran. This study uses the perspective of constructivism and the theory of non-governmental organizations by Lewis Kanji as a basic reference for the research to clarify the role of Iran Human Rights in gathering support for the death of Mahsa Amini. The analysis was conducted by examining books, official journal publications, documents, and news. The results of the study show that to garner support for the case of Mahsa Amini's death, Iran Human Rights carries out an advocacy role, for example creating campaigns, publishing reports and statements, coordinating other human rights organizations, and encouraging diplomatic action. While the operational function plays a role in providing support to the Mahsa Amini family. Despite facing challenges in its implementation, ranging from limited access to information, an unfair justice system, to repression by human rights activists, IHR has proven that they are able to garner support and fight for human rights in Iran for the Amini case by relying on the cooperation of international human rights organizations, advocacy networks, the media, and individuals. Keywords: Iran Human Rights, Mahsa Amini, Islamic Republic of Iran